A Consensus-Based Protocol for Spectrum Sharing Fairness in Cognitive Radio Ad Hoc and Sensor Networks. (24th October 2012) - Hu, Peng; Ibnkahla, Mohamed
Abstract : Spectrum sharing fairness is an important topic in cognitive radio ad hoc networks (CRAHNs) and cognitive radio sensor networks (CRSNs). Consensus-based protocols can provide light-weight and efficient solutions for CRAHNs and CRSNs but the theoretical ground needs to be investigated for spectrum sharing fairness. In this paper, we investigate the convergence condition when applying a consensus-based protocol to spectrum sharing while ensuring spectrum sharing fairness. Based on the local observation and local control scheme using spectrum-related information, an individual cognitive node can effectively perform the spectrum sharing. Then we propose a consensus-based protocol for spectrum sharing. Supported with computer simulation results, we show the effectiveness of using the proposed consensus-based protocol to solve the spectrum sharing problems in CRAHNs and CRSNs.